Epidemiologie a lécba kolorektálního karcinomu v ceských populacních datech - Dusek, L; Hoch, J; Muzík, J; Pavlík, T (Rozhledy v chirurgii, 2009)
The analysis of therapeutic load and evaluation of quality of care require data collected on a long-term basis. The Czech Society for Oncology develops a comprehensive information system that combines data from population-based and clinical registries and that covers all key aspects of health care assessment: monitoring of population risks and associated therapeutic burden, predictions of number of patients to be treated, evaluation of results of diagnostics and of cancer care outcomes. Accessible data proves high cancer burden in the Czech population, colorectal carcinoma being a typical example. Czech population reveals one of the highest incidence of colorectal cancer in the world. Regardless of steadily increasing incidence of colorectal carcinoma, Czech cancer care has managed to stabilize mortality of this disease and also probability of 5-yr relative survival was significantly improved in last 15 years. Developed data base allows to assess burden and results of all therapeutic modalities, including surgery. This work is aimed to present Czech data platform that can be employed in any relevant health care assessment. To keep its position in current financially limited health care system, modern surgery must effectively use all accessible data sources.
Keywords: ženské pohlaví; Female; Colorectal Neoplasms; Česká republika; Incidence; Male; lidé; incidence; mužské pohlaví; Humans; kolorektální nádory; Czech Republic